2016
DOI: 10.1056/nejmoa1504605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artesunate–Amodiaquine on Mortality Related to Ebola Virus Disease

Abstract: Patients who were prescribed artesunate-amodiaquine had a lower risk of death from EVD than did patients who were prescribed artemether-lumefantrine. However, our analyses cannot exclude the possibility that artemether-lumefantrine is associated with an increased risk of death or that the use of artesunate-amodiaquine was associated with unmeasured patient characteristics that directly altered the risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 13 publications
2
107
0
1
Order By: Relevance
“…Plasmodium may bias the antiviral immune response, as this parasite is known to suppress adaptive immunity to heterologous antigens through the hemozoin-induced failure of dendritic cell functions (11). A role of the drug combination used at our ETC in the increased mortality is also a possibility, as suggested by a recent study showing a decrease in mortality in artesunate-amodiaquine-treated EVD patients compared with artesunate-lumefantrine-treated ones (12). Indeed, this treatment may be harmful because of the risk of prolongation of QT-interval and of fatal arrhythmias in patients presenting hypokalemia or hypomagnesemia.…”
Section: Discussionmentioning
confidence: 94%
“…Plasmodium may bias the antiviral immune response, as this parasite is known to suppress adaptive immunity to heterologous antigens through the hemozoin-induced failure of dendritic cell functions (11). A role of the drug combination used at our ETC in the increased mortality is also a possibility, as suggested by a recent study showing a decrease in mortality in artesunate-amodiaquine-treated EVD patients compared with artesunate-lumefantrine-treated ones (12). Indeed, this treatment may be harmful because of the risk of prolongation of QT-interval and of fatal arrhythmias in patients presenting hypokalemia or hypomagnesemia.…”
Section: Discussionmentioning
confidence: 94%
“…Of the 4 case studies, 2 studies52, 53 were judged to have poor reporting quality, 1 study 55 was judged to have fair reporting quality, and the last study 54 had good reporting quality. All the nonrandomized cohort studies51, 56, 57, 58, 59 were found to have a low risk of bias.…”
Section: Resultsmentioning
confidence: 95%
“…This resulted in 11 drug screening,23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33 17 preclinical studies,34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 and 9 clinical studies 51, 52, 53, 54, 55, 56, 57, 58, 59…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Docking studies highlighted the FDA-approved antimalarials CQ and amodiaquine (Fig. 139 Other compounds with the pyrrolidinone scaffold were also reported. 21,138 However, as already mentioned, a few studies showed that CQ was not able to increase the survival rate either in animals or in EVD patients.…”
Section: Vp35 Inhibitorsmentioning
confidence: 96%